Effect of muscle tension type on lower limb blood flow and dynamics of lung volume rates when mastering punching technique in boxing - Neupokoev, S. N.; Bredikhina, Y. P.; Shilko, V. G. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to assess the influence of various types of muscle tension on lower limb blood flow and external respiration rates of skilled boxers when they perform punches.